Isolation and Cryopreservation of Placental Cells: Search for Optimal Biotechniques in Experimental and Regenerative Medicine - Prokopiuk, Olga; Shevchenko, Mariia; Prokopiuk, Volodymyr; Musatova, Irina; Safonov, Roman; Prokopiuk, Oleksandra (Problems of Cryobiology and Cryomedicine, 2021)
High efficacy of placental cells application necessitates their investigation. Preclinical studies require an improvement of the methods for obtaining, standardizing and storage of placental cells of experimental animals. Cells were isolated from rats and mice placentas by means of different enzymatic methods and the one of explants. Cells were cryopreserved with DMSO in DMEM using two-stage freezing. The number, morphological, cultural, metabolic features of cells were studied after isolation and storage. The maximum number of viable cells from the placentas of mice and rats was found to be obtained using the explant method or trypsin with ETDA. Cell cultures from mice and rats placentas after the third passage had stable morphofunctional characteristics. The viability of warmed rat placental cells according to dye exclusion was (92.3 ± 1.6)%, according to the adhesive test this was (81.3 ± 5.8)%. For mice placental cells, these values were (86.7 ± 3.7)% and (79.2 ± 8.1)%, correspondingly. The research results enabled the determining of effective biotechniques for obtaining the cryopreserved placental cells of rats and mice to perform preclinical studies of their biological effect in models of allo- and autotransplantations. Probl Cryobiol Cryomed 2021; 31(1): 082–088